DESIGN AND EVALUATION OF SURFACING CONDITION OF BUS STOP PAVEMENTS (Perner's Contacts, 2011)
The paper deals with the problematic of pavement design and surfacing evaluation of the urban bus stops. The most attention is paid to the asphalt pavements, sett paving and its historical development, as well as their design itself, according to the technical conditions 170 valid in Czech Republic, because in Slovakia there are no such conditions available. In the practical part, the paper evaluates and solves condition of selected 37 bus stops in the city of Žilina (1). As a conclusion, the paper provides recommendations for design of urban bus stops for a consideration of realized monitoring.
Keywords: bus stop; pavement; surfacing; transverse unevenness